Optimization of Productive Waqf Management in Pekanbaru, Indonesia - Nuryanti, Nuryanti; Lubis, Haniah (Dinar : Jurnal Ekonomi dan Keuangan Islam, 2025)
This study aims to identify ways to optimize the management of productive waqf through the collaboration of stakeholders, including government, academics, and the community. This research uses a qualitative descriptive method with data collection through focused group discussion (FGD) and interviews with nazir, wakif, and related agencies. The results showed that the optimization of waqf management requires the active role of all parties to ensure that waqf management runs transparently and productively. Waqf education and literacy through digital media, including the use of Quick Response Code (QR Code), as well as digital payment platforms such as Link Aja Syariah and OVO, are the main strategies in increasing waqf awareness. Nazir is also required to run a transparent program with detailed and measurable reporting of funds. This study recommends increasing nazir capacity, revising regulations related to incentives for waqf managers, and encouraging active participation of academics and the government in the development of more effective productive waqf.